A qualitative study of innovativeness, strategies and leadership styles of successful women entrepreneurs in Malaysia - Cheng, Wei Hin; Md Isa, Filzah; Hashim, Norashidah (2012)
Women entrepreneurs play an important role in the development of a country’s economy.Women today made up more than forty percent of the labor force in Malaysia.Past research on entrepreneurs demonstrated that individuals with innovative behavior, strategies and leadership distinguished them from non entrepreneurs.This research was done to explore entrepreneurial innovative behavior leadership styles and strategies of successful women entrepreneurs in Malaysia.It is a qualitative research which involved interviews with successful women entrepreneurs.Strategies on how they expand their business were also examined..